Development and validation of the multidimensional motivational climate observation system - Smith, N.; Tessier, D.; Tzioumakis, Y.; Quested, Eleanor; Appleton, P.; Sarrazin, P.; Papaioannou, A.; Duda, J. (2015)
This article outlines the development and validation of the Multidimensional Motivational Climate Observation System (MMCOS). Drawing from an integration of the dimensions of the social environment emphasized within achievement goal theory and self-determination theory (as assumed within Duda's [2013] conceptualization of "empowering" and "disempowering" climates), the MMCOS was developed to enable an objective assessment of the coach-created motivational environment in sport. Study 1 supported the initial validity and reliability of the newly developed observation system. Study 2 further examined the interobserver reliability and factorial structure of the MMCOS. Study 3 explored the predictive validity of the observational system in relation to athletes' reported basic psychological need satisfaction. Overall, the results of these studies provide preliminary support for the inter- and intraobserver reliability, as well as factorial and predictive validity of the MMCOS. Suggestions for the use of this observational system in future research in sport are provided.